2015
DOI: 10.1016/j.cortex.2015.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating hyper and hypoself biases to a core self-representation

Abstract: Biases to favour self-related information over information related to other people have been demonstrated across a range of both high- and low-level tasks, but it is unclear whether these tasks 'tap' the same types of self representation. Here we assess results from two patients with damage primarily to (i) left ventro-medial prefrontal (vmPFC) cortex and the insula (patient SC), and (ii) temporo-parietal (TP) cortex (patient RR). We report evidence from both low-level perceptual matching tasks and episodic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…Neuropsychological evidence also supports the argument for the distinct, and sometimes antagonistic effects of self‐attention and task‐based, executive attention, and for the critical role of the mPFC and the LpSTS in self‐based attention. Sui et al . report data from two patients, one with damage to the mPFC and one with more posterior damage involving the LpSTS.…”
Section: The Neural Basis Of Self‐reference Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychological evidence also supports the argument for the distinct, and sometimes antagonistic effects of self‐attention and task‐based, executive attention, and for the critical role of the mPFC and the LpSTS in self‐based attention. Sui et al . report data from two patients, one with damage to the mPFC and one with more posterior damage involving the LpSTS.…”
Section: The Neural Basis Of Self‐reference Effectsmentioning
confidence: 99%
“…Neuropsychological evidence also supports the argument for the distinct, and sometimes antagonistic effects of self-attention and task-based, executive attention, and for the critical role of the mPFC and the LpSTS in self-based attention. Sui et al 81 report data from two patients, one with damage to the mPFC and one with more posterior damage involving the LpSTS. They found that self-bias effects on perceptual matching were reduced in the patient with the mPFC lesion, consistent with damage to the self-representation critical to "drive" attention to self-related items.…”
Section: ) (B) Self-expansion In Perception the Figure Is About Tmentioning
confidence: 99%
“…These data indicate that attentional-control processes are recruited more strongly in the latter condition (see Sui & Humphreys, 2015a, for a discussion). Additionally, neuropsychological studies have shown that brain lesion over the VMPFC abolishes self biases in memory, whereas brain damage in the dorsal attentional-control network that spares the VMPFC generates abnormally large biases toward self-related stimuli, due to an exaggerated effect of strong attentional signals (Sui, Enock, Ralph, & Humphreys, 2015). Researchers have argued that self-bias effects are determined by the interaction between the ventral network through the VMPFC and the dorsal attentional-control network for control of behavior (Sui, 2016).…”
mentioning
confidence: 99%
“…This would not fit with available neuropsychological evidence (Sui, Enock, Ralph, & Humphreys, 2015). These lesion data show that damage to pSTS increases self-bias effects, while damage to vmPFC decreases them.…”
Section: Please Scroll Down For Articlementioning
confidence: 73%